Multi-scale pore fractal characteristics of differently ranked coal and its impact on gas adsorption - Li, Zhongbei; Ren, Ting; Li, Xiangchun; Qiao, Ming; Yang, Xiaohan; Tan, Lihai; Nie, Baisheng (International journal of mining science and technology, 2023)
Well-developed pores and cracks in coal reservoirs are the main venues for gas storage and migration. To investigate the multi-scale pore fractal characteristics, six coal samples of different rankings were studied using high-pressure mercury injection (HPMI), low-pressure nitrogen adsorption (LPGA-N2), and scanning electron microscopy (SEM) test methods. Based on the Frankel, Halsey and Hill (FHH) fractal theory, the Menger sponge model, Pores and Cracks Analysis System (PCAS), pore volume complexity (Dv), coal surface irregularity (Ds) and pore distribution heterogeneity (Dp) were studied and evaluated, respectively. The effect of three fractal dimensions on the gas adsorption ability was also analyzed with high-pressure isothermal gas adsorption experiments. Results show that pore structures within these coal samples have obvious fractal characteristics. A noticeable segmentation effect appears in the Dv1 and Dv2 fitting process, with the boundary size ranging from 36.00 to 182.95 nm, which helps differentiate diffusion pores and seepage fractures. The D values show an asymmetric U-shaped trend as the coal metamorphism increases, demonstrating that coalification greatly affects the pore fractal dimensions. The three fractal dimensions can characterize the difference in coal microstructure and reflect their influence on gas adsorption ability. Langmuir volume (VL) has an evident and positive correlation with Ds values, whereas Langmuir pressure (PL) is mainly affected by the combined action of Dv and Dp. This study will provide valuable knowledge for the appraisal of coal seam gas reservoirs of differently ranked coals.